Contextualizing international ambidextrous strategies of Chinese multinational enterprises. (10th March 2022) - Avioutskii, Viatcheslav; Tensaout, Mouloud
Abstract: This article helps explain the theoretical mechanisms of the contextual influence of ambidextrous foreign acquisition strategies of Chinese multinational enterprises (MNEs) in Europe. Based on the National Business System approach, we demonstrate that these strategies are contextually driven and institutionally conditioned. We use fuzzy‐set qualitative comparative analysis to identify the configurations of factors affecting the strategies of 829 mergers and acquisitions (M&As) in 29 countries in 1992–2019. We propose a new measure for the organizational ambidexterity construct based on the nature and type of M&As. Our results show that conglomerate affiliation, state ownership, and international business experience affect the deployment of ambidextrous acquisition strategies, while outward foreign direct investment (FDI) policies have a positive effect only for individual firms or when host country innovation environment is well developed. Finally, smaller individual MNE early internationalizers are more likely to deploy acquisition ambidexterity when the government adopts outward FDI policies.